Academic burnout and student engagement: a moderated mediation model of internal locus of control and loneliness. Issue 2 (4th December 2020) - Singh, Lata Bajpai; Kumar, Alok; Srivastava, Shalini
Abstract : Purpose: This paper aims to assess the relationship between academic burnout-student engagement relationships on management students of the Delhi-NCR region of Northern India. It further attempts to study the moderating impact of internal locus of control and mediating impact of loneliness on the academic burnout-student engagement relationship. Design/methodology/approach: The data was collected using standardized instruments from 264 respondents. Descriptive statistics, correlation and moderated-mediated regression analysis were used to test the hypotheses. Findings: The study found a negative association between student engagement and academic burnout and loneliness. A positive association between academic burnout and loneliness and a moderating impact of internal locus of control on academic burnout and student engagement relationship. Loneliness acted as a partial mediator for the moderated relationship between the academic burnout-student engagement relationship. Research limitations/implications: Sample size and sampling units are the limitations of the study. Practical implications: The conclusion of the presented study offers different inferences including validating the self-determination theory (Ryan and Deci, 2000) and possible courses of actions to be taken by academic institutions and students themselves. It ranges from careful investigation of student's behaviors, design and implements collaborative projects along with student's involvement in social networking based groups for collaborations and help. Social implications: With the help of the study, the society including parents, family, friends, officials and academicians at educational institutions can offer useful insights to students through recreational and social activities for behavior modifications. Originality/value: The major contribution of the study is to understand the psyche of the budding professionals perceiving increased stress and pressure. Limited studies are found in the Indian context and no studies in the past have used the study variables together. Internal locus of control as a personality variable has not been studied with respect to student's burnout and engagement. Furthermore, none of the studies done in the past have deliberated upon loneliness with respect to the student community.